Gaining prediction accuracy in land use modeling by integrating modeled hydrologic variables. (May 2019) - Wagner, Paul D.; Fohrer, Nicola
Abstract: Land use and hydrology are interdependent, so that land use modeling could benefit from hydrologic modeling. This study aims to integrate spatial predictions of hydrologic variables as provided by a hydrologic model into a land use model for a rapidly urbanizing catchment in India. The benefits of this integration are quantified by comparing predictions of a land use model that uses a basic set of explanatory variables to a land use model that additionally uses the modeled hydrologic variables. Our results indicate that the integration of the hydrologic variables improved the model accuracy indicated by overall accuracy (+3 and + 4 percentage points (pp)), class specific user and producer accuracies (up to +8 pp) and figure of merit (+4 and + 5.3 pp) when compared with land use classifications at two points in time. Moreover, the land use patterns show that the integration of the hydrologic variables helped to avoid allocation errors. Highlights: Hydrologic variables modeled with SWAT improved CLUE-s model simulations. A more reasonable allocation was achieved for a future scenario. We recommend to integrate land use models and hydrologic models.